A meta-analysis examining the nature of trade-offs in microfinance. (3rd July 2018) - Reichert, Patrick
Abstract: This meta-analysis reviews existing evidence on the ability of microfinance institutions (MFI) to achieve social and financial goals simultaneously. Through an initial screen of 3088 articles covering empirical tests on microfinance performance trade-offs, I synthesize 623 empirical findings from 61 studies to identify the dimensions of MFI performance, and study characteristics associated with trade-offs between financial and social objectives Overall, findings suggest that depth of outreach, cost of outreach, and efficiency indicators increase the prevalence of trade-offs, while risk indicators are associated with fewer trade-offs. Profitability indicators and outreach to women are found to have no significant effect on performance trade-offs. Additionally, study characteristics suggest that using an economic frontier methodology or publishing in development journals increases the incidence of trade-offs, while time trends reveal that trade-offs become less acute as the industry matures. Consequently, MFIs face difficult decisions in relation to the possibility that social goals need be sacrificed to achieve financial sustainability.